Kajian Kerjasama antar Pemangku Kepentingan dalam Program Pengembangan Klaster Tanaman Obat (Biofarmaka) di Kecamatan Tengaran Kabupaten Semarang Tahun 2011-2013 - hani, dea aprilaga; Widayati, Wiwik; Taufiq, Ahmad (Journal of Politic and Government Studies, 2015)
Behind the many benefits and market demand for medicinal plants, the fate of medicinal plant farmers are still not enough prosperous. Therefore, the government has taken an initiative for the welfare of the medicinal plant farmers by initiated a policy that tends to support them. One of the policy was made by the Bank Indonesia which is invites other stakeholders such as BPN Central Java, Central Java Dinasperindag, BRI branch Ungaran, Plantation Office of Semarang regency, and PT. Sido Muncul in a program named